2022
DOI: 10.1002/iid3.737
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein hydrolysate mitigates both inflammation and endotoxin tolerance in THP‐1 human monocytic leukemia cells

Abstract: Introduction: It is important to control both inflammation and immunosuppression after severe insults, such as sepsis, trauma, and surgery. Endotoxin tolerance is one of the immunosuppressive conditions and it has been known that endotoxin tolerance relates to poorer clinical outcomes in patients with severe insults. This study investigated whether whey protein hydrolysate (WPH) mitigates inflammation and endotoxin tolerance in THP-1 human monocytic leukemia cells.Methods: Endotoxin tolerance can be experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Corrochano et al quantified mRNA transcripts of the antioxidant genes SOD1 and CAT in intestinal cells that had been treated with 2.5 mg/mL of gastrointestinal bovine whey proteins (corresponding to the SW-Ds in our study) [ 76 ]. A recent study by Ishikawa evaluated some genes (e.g., IL6 and IL10 ) implicated in inflammation and immunosuppression in THP-1 cells stressed with LPS and treated with 5 mg/mL of a whey protein hydrolysate [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Corrochano et al quantified mRNA transcripts of the antioxidant genes SOD1 and CAT in intestinal cells that had been treated with 2.5 mg/mL of gastrointestinal bovine whey proteins (corresponding to the SW-Ds in our study) [ 76 ]. A recent study by Ishikawa evaluated some genes (e.g., IL6 and IL10 ) implicated in inflammation and immunosuppression in THP-1 cells stressed with LPS and treated with 5 mg/mL of a whey protein hydrolysate [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Promising results emerged from studies on whey protein hydrolysate (WPH). Experiments with human monocytic leukemia cells (THP-1) revealed potential benefits of WPH on inflammation and endotoxin tolerance by modulating the immune response, and reducing IL-6 and IL-10 levels [ 83 ]. An analysis by Kamal et al [ 84 ] showed that camel milk-derived WPH inhibits the production of proinflammatory cytokines like IL-8 and displays antiproliferative activity against liver cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation might be that certain molecular dietary components stimulated the tnfa expression. For instance, exposure to whey protein hydrolysate, which is an ingredient of the diet used in the present experiment, increased the tnfa levels in human monocytic leukaemia cells [ 40 ]. However, we did not register an upregulation of other immune-related genes in response to the onset of feeding.…”
Section: Discussionmentioning
confidence: 99%